Molecular phylogenetic position of endangered Wilfredomys within Sigmodontinae (Cricetidae) based on mitochondrial and nuclear DNA sequences and comments on Wiedomyini - Machado, Leonardo Ferreira; Passaia, Milena Henrique; Rodrigues, Fernando Pacheco; Peters, Felipe Bortolotto; Sponchiado, Jonas; Valiati, Victor Hugo; Christoff, Alexandre Uarth (Zootaxa, 2015)
Wilfredomys, a monotypic genus of endangered sigmodontine rats, was historically related to the tribe Thomasomyini or considered “incertae sedis”. Given no molecular data is available for Wilfredomys, the phylogenetic position of this taxon is uncertain in relation to modern, molecular hypotheses of sigmodontine relationships. We investigate the phylogeny of Wilfredomys to provide a hypothesis of its position within Sigmodontinae based on nuclear and mitochondrial DNA sequences. Bayesian and maximum likelihood phylogenetic analyses recovered Wilfredomys oenax as sister to Wiedomys pyrrhorhinos, and Wie. cerradensis fell out sister to this clade. At the genus level, Phaenomys is sister to Wilfredomys + Wiedomys, forming a novel and well-supported sigmodontine clade. Our results suggest that tribe Wiedomyini should encompass Wilfredomys in addition to Wiedomys and Cholomys, thus the hypothesis that Wiedomys is paraphyletic should be investigated further. Another plausible classification scheme consistent with our results would be to expand Wiedomyini to encompass the clade composed of Phaenomys + Wilfredomys + Wiedomys. Last, our recovery of an “Atlantic clade” composed of lineages restricted to eastern South America supports the idea that this region has likely played an important role in sigmodontine diversification.